2019
DOI: 10.1177/1745506519890969
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive analysis of health practices, barriers to healthcare and the unmet need for cervical cancer screening in the Lower Napo River region of the Peruvian Amazon

Abstract: Objectives:To undertake an descriptive analysis of the health needs, healthcare practices and barriers to accessing healthcare faced by women in Lower Napo River Region, Peru, and to understand health literacy regarding cervical cancer and the need for more effective cervical cancer screening services.Methods:We performed a community-based needs assessment adapting Demographic and Health survey methodology with additional questions determining female health literacy on cervical cancer and assessing the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
3
14
0
7
Order By: Relevance
“…We further observed that access to mass media showed decreased odds of healthcare accessibility barriers, which confirms previous studies in Ethiopia [47], India [48], Bangladesh [49], and rural Malawi [50]. The reason for this could be that listening to the radio and watching television increases ones' health literacy, which has been identified as key to healthcare utilization [51].…”
Section: Discussionsupporting
confidence: 88%
“…We further observed that access to mass media showed decreased odds of healthcare accessibility barriers, which confirms previous studies in Ethiopia [47], India [48], Bangladesh [49], and rural Malawi [50]. The reason for this could be that listening to the radio and watching television increases ones' health literacy, which has been identified as key to healthcare utilization [51].…”
Section: Discussionsupporting
confidence: 88%
“…Exposure to mass media also showed decreased odds of healthcare accessibility barriers, which corroborates earlier studies in Ethiopia [40], India [41], Bangladesh [42], and rural Malawi [43]. The reason for this could be that listening to radio, reading newspaper, and watching television increase ones' health literacy, which has been identified as a key enabler to healthcare utilization [44].…”
Section: Plos Onesupporting
confidence: 85%
“…Another study focusing on unmet needs in Brazil found that financial reasons, long waiting times and lack of professionals and services were main reasons for forgoing appropriate care (31). Qualitative research further indicates that factors associated with poorer access are interconnected, such that people experiencing multiple vulnerability factors may have even greater barriers to health services, which require coordinated action of multiple sectors beyond health (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%